Breakpoint chlorination and free-chlorine contact time: Implications for drinking water N-nitrosodimethylamine concentrations - Charrois, Jeffrey; Hrudey, S. (IWA Publishing, 2007)
North American drinking water utilities are increasingly incorporating alternative disinfectants, such as chloramines, in order to comply with disinfection by-product (DBP) regulations. N-Nitrosodimethylamine (NDMA) is a non-halogenated DBP, associated with chloramination, having a drinking water unit risk two to three orders of magnitude greater than currently regulated halogenated DBPs. We quantified NDMA from two full-scale chloraminating water treatment plants in Alberta between 2003 and 2005 as well as conducted bench-scale chloramination/breakpoint experiments to assess NDMA formation. Distribution system NDMA concentrations varied and tended to increase with increasing distribution residence time. Bench-scale disinfection experiments resulted in peak NDMA production near the theoretical monochloramine maximum in the subbreakpoint region of the disinfection curve. Breakpoints for the raw and partially treated waters tested ranged from 1.9:1 to 2.4:1 (Cl2:total NH3-N, M:M). Bench-scale experiments with free-chlorine contact (2 h) before chloramination resulted in significant reductions in NDMA formation (up to 93%) compared to no free-chlorine contact time. Risk-tradeoff issues involving alternative disinfection methods and unregulated DBPs, such as NDMA, are emerging as a major water quality and public health information gap.